Ecogenomics of microbial communities in bioremediation of chlorinated contaminated sites - Maphosa, Farai; Lieten, Shakti H.; Dinkla, Inez; Stams, Alfons J.; Smidt, Hauke; Fennell, Donna E. (Frontiers in Microbiology, 2012)
Organohalide compounds such as chloroethenes, chloroethanes and polychlorinated benzenes are among the most significant pollutants in the world. These compounds are often found in contamination plumes with other pollutants such as solvents, pesticides and petroleum derivatives. Microbial bioremediation of contaminated sites, has become commonplace whereby key processes involved in bioremediation include anaerobic degradation and transformation of these organohalides by organohalide respiring bacteria and also via hydrolytic, oxygenic and reductive mechanisms by aerobic bacteria. Microbial ecogenomics has enabled us to not only study the microbiology involved in these complex processes but also develop tools to better monitor and assess these sites during bioremediation. Microbial ecogenomics have capitalized on recent advances in high-throughput and -output genomics technologies in combination with microbial physiology studies to address these complex bioremediation problems at a system level. Advances in environmental metagenomics, transcriptomics and proteomics have provided insights into key genes and their regulation in the environment. They have also given us clues into microbial community structures, dynamics and functions at contaminated sites. These techniques have not only aided us in understanding the lifestyles of common organohalide respirers, for example Dehalococcoides, Dehalobacter and Desulfitobacterium, but also provided insights into novel and yet uncultured microorganisms found in organohalide respiring consortia. In this paper we look at how ecogenomic studies have aided us to understand the microbial structures and functions in response to environmental stimuli such as the presence of chlorinated pollutants.